Africa Agriculture Transformation Scorecard: performance and lessons. Eswatini - Fakudze, Bhekiwe; Matchaya, Greenwell C.; Greffiths, Ikhothatseng Jacob; Mbuyisa, H. (Regional Strategic Analysis and Knowledge Support System for Eastern and Southern Africa, 2023)
The Malabo Declaration on accelerated agricultural growth and transformation for shared prosperity and improved livelihoods is a set of goals that were adopted by Heads of State and Government of the African Union in 2014 in Malabo, Equatorial Guinea (AUC 2014). To translate the seven Malabo commitments into results, a call for action was made by the Heads of State and Governments, by calling upon the AU Commission and the NEPAD Planning and Coordinating Agency, in collaboration with partners, to initiate a review process to be conducted on a biennial basis starting 2017, with an objective of tracking, measuring, and reporting progress towards achieving the Malabo Declaration commitments by 2025. Three Biennial Reviews (BR) have been conducted—the inaugural BR in 2017, the second BR in 2019, and the third and most recent BR in 2021. This brief draws on the third BR report to summarize the performance of Eswatini in pursuit of the seven Malabo Declaration commitments. It also reviews policy, programmatic, and investment changes in Eswatini induced by the 2017, 2019, and 2021 BR cycles, highlighting policy actions and programmatic measures Eswatini must take to meet its Malabo Declaration commitments by 2025. The third BR report shows that Eswatini is not on-track to achieve the Malabo commitments by 2025. This is a setback for the country because, in the first BR, the country’s overall score was above the minimum benchmark, indicating that the country then was on-track to achieve the Malabo targets. A key recommendation from the analysis is for the government to accelerate the development of the second-generation instrument-based NAIP and the monitoring and evaluation system for the investment plan. The country needs to improve its performance on the overall CAADP process and implement CAADP-based policy and institutional support plans, as deficiencies in this support led to lower scores on this Malabo commitment.